Using a Literacy Based Behavioral Intervention to Teach College Students with Intellectual and Developmental Disabilities to Request a Classroom Accommodation. Issue 2 (March 2021) - Hall Pistorio, Kalynn; Kearney, Kelly B.; Eshman, Shannon; Thomas, Kelly; Carey, Gwendolyn
Many individuals with an intellectual and developmental disabilities (IDD) are attending postsecondary education programs, yet they are not always proficient in using self-advocacy skills, such as requesting an academic accommodation. Access to these accommodations is vital for success in the postsecondary settings. Literacy based behavioral interventions (LBBIs) use a combination of print, visuals, and rehearsal and are an effective tool for teaching a range of skills including job skills to this population, but have not been investigated with a self-advocacy skill. In this study, a pre-service teacher was taught to deliver an LBBI to postsecondary students with IDD so they would learn to request and use a free online tool to record class lectures. Results showed that students were able to master the skill with the pre-service teacher delivered LBBI and maintain the skill after removal of the LBBI.